Functional changes of the small intestine in over- and undernourished suckling rats support the development of obesity risk on a high-energy diet in later life - Mozes, S; Šefčíková, Z; Lenhardt, L (Physiological research, 2007)
To investigate the relationship between early nutritional experience, ontogeny of the small intestinal functions and predisposition to obesity development, the following experimental models of male Sprague-Dawley rats were used: 1) rats in which the quantity of nutrition was manipulated from birth to weaning (day 30) by adjusting the number of pups in the nest to 4 (SL), 10 (NL) and 16 pups (LL) and 2) littermates of SL, NL and LL rats fed either a standard or a hypercaloric diet from days 80 to 135 of age. The overfed SL pups were overweight after day 15 and became permanently obese, whereas the underfed smaller LL pups, due to accelerated growth and enhanced food intake from day 30 to day 35, attained a body fat level that did not differ from normally fed NL rats. Moreover, a significantly increased duodenal and jejunal alkaline phosphatase (AP) activity was found in SL and LL rats and these acquired somatic and intestinal characteristics persisted from weaning throughout life. Eight weeks of high-energy diet feeding elicited a similar pattern of intestinal response in SL and LL rats that was clearly different from NL rats. Despite energy over-consumption in these three groups, both SL and LL rats still displayed enhanced AP activity and showed a significant increase in protein/DNA ratio accompanied with a significant body fat accretion. These results indicate that the postnatally acquired small intestinal changes induced by over- and undernutrition could be involved in the similar predisposition to obesity risk in later life when caloric density of the diet is raised.
Keywords: Animals; energetický příjem; Malnutrition; Aging; dietní tuky; Intestine, Small; Obesity; alkalická fosfatasa; kojená zvířata; Energy Intake; nadměrná výživa; podvýživa; Rats, Sprague-Dawley; Risk Factors; tělesná hmotnost; Animals, Suckling; obezita; Male; potkani Sprague-Dawley; fyziologie výživy zvířat; stárnutí; Animal Nutritional Physiological Phenomena; rizikové faktory; krysa rodu Rattus; Body Weight; Alkaline Phosphatase; zvířata; tuková tkáň; mužské pohlaví; Dietary Fats; Rats; Overnutrition; tenké střevo; Adipose Tissue